2014
DOI: 10.1007/s11033-014-3146-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity and circulating adipose stromal cells among breast cancer survivors

Abstract: A positive association of obesity with breast cancer incidence and mortality is well established. Recent reports indicate that adipose stromal cells (ASCs) play an important role in breast cancer development and progression by producing estrogens and tumor-promoting cytokines. Furthermore, circulating ASCs have been uniquely detected in obese individuals, which is likely due to increased tissue remodeling and cell mobilization. The number of circulating ASCs is even more prominent in obese patients with colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 84 publications
1
15
0
Order By: Relevance
“…We have shown that ASC mobilized from WAT in obese mice are recruited by tumors and support their vascularization and growth . Consistent with that notion, our clinical studies have provided evidence that ASC are systemically mobilized in obesity . While a growing body of evidence indicates the role of ASC in mediating obesity pathophysiology, molecular mechanisms that govern ASC trafficking have remained obscure .…”
Section: Introductionsupporting
confidence: 77%
“…We have shown that ASC mobilized from WAT in obese mice are recruited by tumors and support their vascularization and growth . Consistent with that notion, our clinical studies have provided evidence that ASC are systemically mobilized in obesity . While a growing body of evidence indicates the role of ASC in mediating obesity pathophysiology, molecular mechanisms that govern ASC trafficking have remained obscure .…”
Section: Introductionsupporting
confidence: 77%
“…ASC migrate to tumors in response to tumor production of CXCL1 and CXCL8 (34). The application of these pre-clinical findings to human disease was evidenced by data indicating that obese prostate cancer patients have increased tumor CXCL1 expression, circulating ASC, and tumor-infiltrating ASC (34) and has been further demonstrated by studies indicating an increase in circulating mesenchymal stromal cells (which include ASC) in obese disease-free donors (35) and colorectal cancer patients (36) as well as an increase in circulating ASC in obese breast cancer survivors (37). …”
Section: Introductionmentioning
confidence: 97%
“…ASCs were collected from the blood samples and analyzed as previously described [8]. Briefly, blood samples were centrifuged at room temperature for 25 min with no brake at 1600 × g .…”
Section: Methodsmentioning
confidence: 99%
“…Circulating Adipose Stromal Cells (ASCs) have been linked to cancer recurrence risk [6,7]. Our previous work has shown higher levels of ASCs in obese BCSs [8]. Furthermore, excess body fat has been shown to promote cancer in postmenopausal women by increasing levels of inflammation, insulin, and other hormones [9].…”
Section: Introductionmentioning
confidence: 99%